The contrarians: Are they really the winner? - Novi Budiarso; Winston Pontoh (Yayasan Widyantara Nawasena Raharja, 2023)
Several new global issues information (including the COVID-19 pandemic) tends to have an impact on the capital market in Indonesia but big-cap stocks show good performance compared to small-cap stocks. Employing 766 listed firms as sample with 246 market days, this study examines whether the contrarians are really the winner. This study finds that the contrarians succeed to beat the market by violating the efficient market hypothesis. However, the success of the contrarian strategy does not seem to indicate that they are the real winners as they are only thin-winning.